2018
DOI: 10.3892/mmr.2018.9768
|View full text |Cite
|
Sign up to set email alerts
|

A risk assessment model for the prognosis of osteosarcoma utilizing differentially expressed lncRNAs

Abstract: The present study was conducted to establish a risk assessment model for evaluating osteosarcoma prognosis based on prognosis-associated long non-coding RNA (lncRNA) expression. Human osteosarcoma expression profiles were obtained from the NCBI GEO and EBI ArrayExpress databases and differently expressed lncRNAs between good and poor prognosis groups were evaluated using Student's t-test and Wilcoxon rank test in R (v. 3.1.0). A multivariate Cox regression was used to establish a risk assessment system based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…1 A). A previous study found that higher LINC00987 expression was strongly correlated with the lower overall survival of osteosarcoma [ 9 ]. In this study, the expression of LINC00987 was consistent with previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A). A previous study found that higher LINC00987 expression was strongly correlated with the lower overall survival of osteosarcoma [ 9 ]. In this study, the expression of LINC00987 was consistent with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…This study provides evidence that LINC00987 is an oncogene and therapeutic target. A previous study found that LINC00987 expression was increased in patients with acute myeloid leukemia and osteosarcoma and was closely related to poor prognosis [ 9 , 17 ]. These studies also support that LINC00987 is an oncogene, similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of new OS biomarkers is of great significance for the treatment and prognosis of OS. Apart from disease genes, many studies have shown that lncRNAs also play an important role in the development of OS [30,35]. In this study, we sequenced 11 pairs of OS samples and screened potential susceptibility genes and lncRNAs of OS by bioinformatics methods and clinical indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research showed that TTK overexpression is correlated with large tumour size and advanced clinical stage of osteosarcoma patients 20 . Bioinformatic study identified TTK among the top genes driving osteosarcoma development and predictive of poor prognosis 21 . However, the molecular mechanism underlying the function of TTK in osteosarcoma has never been systematically investigated and remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%